2023
DOI: 10.3390/nu15092216
|View full text |Cite
|
Sign up to set email alerts
|

Young Japanese Underweight Women with “Cinderella Weight” Are Prone to Malnutrition, including Vitamin Deficiencies

Katsumi Iizuka,
Hiroko Sato,
Kazuko Kobae
et al.

Abstract: Undernutrition among young women at “Cinderella weight” is socially important in Japan. To determine the nutritional status of Cinderella-weight women, we conducted an exploratory cross-sectional study on the health examination results of employees aged 20 to 39 (n = 1457 and 643 for women and men, respectively). The percentage of underweight women was found to be much higher than that of men (16.8% vs. 4.5%, respectively). In underweight women (n = 245), handgrip strength (22.82 ± 5.55 vs. 25.73 ± 5.81 kg, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…A low BMI is also associated with anemia, low sex hormone concentrations, low bone density, hypotension, and feelings of fatigue and malaise [1]. We have also reported that young women who are underweight are predisposed to deficiencies in vitamins B1, B12, and D and folate [2]. This change was also observed in underweight women older than 40 years.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A low BMI is also associated with anemia, low sex hormone concentrations, low bone density, hypotension, and feelings of fatigue and malaise [1]. We have also reported that young women who are underweight are predisposed to deficiencies in vitamins B1, B12, and D and folate [2]. This change was also observed in underweight women older than 40 years.…”
Section: Discussionmentioning
confidence: 92%
“…Young women in Japan have lower body masses than women in Western countries [1][2][3][4][5]. The health risks associated with underweight individuals are generally underestimated in comparison with those associated with overweight individuals in routine practice, especially in preventive medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron-deficiency anemia is a serious health issue due to the desire for thinness among young women in Japan [66]. Underweight young women in Japan also exhibit a low intake of dietary fiber, calcium, iron, and vitamin D [67]. Thus, protein, dietary fiber, calcium, iron, and vitamin D were deemed the main nutrients to encourage in the Meiji NPS.…”
Section: Selection Of Nutrients To Encouragementioning
confidence: 99%